Ok.... i^2 = -1, so I rule that i = -1^.5. So, i^2 = -1^.5 * -1^.5 should equal -1, being i squared. But, I can simplify that to i^2 = (-1*-1)^.5, and then to i^2 = 1^.5, which simplifies to i^2 = 1, and i = 1.
2006-10-05
13:11:46
·
5 answers
·
asked by
Anonymous
in
Science & Mathematics
➔ Mathematics
Ok.... i^2 = -1, so I rule that i = -1^.5. So, i^2 = -1^.5 * -1^.5 should equal -1, being i squared. But, I can simplify that to i^2 = (-1*-1)^.5, and then to i^2 = 1^.5, which simplifies to i^2 = 1, and i = 1.
f_m - but what about the property that states
a^y * b^y = ab^y
? Or did I remember that wrong?
2006-10-05
13:26:33 ·
update #1
Thanks, bandf. That's pretty much the best answer out of all the people I've asked this, even from mathforum.org =)
2006-10-05
13:34:24 ·
update #2